Model Hubungan Citra Merek, Perpsepsi Kualitas, Harga dan Intensi Pembelian Konsumen - Hendryadi Hendryadi; Diana Purnamasari (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2018)
This study examines the relationship between brand image, perceived quality, and price on the purchase intention of brand X perfume. In particular, the role of quality and price is placed as a mediator on the relationship between brand image and purchase intention. Data were collected through the distribution of questionnaires with the convenience sampling method. A total of 117 customers from three supermarkets in Jakarta were used as respondents. Data analysis used PLS-SEM to test the proposed hypothesis. Empirical results show that brand image significantly and positively affects perceptions of quality and price. Brand image, quality, and price are three factors that directly affect purchase intention. Testing the mediation model shows that price is proven to be a mediator of the relationship between brand image and purchase intention, while perceived quality is not significant. This research is limited to the buying behavior of perfume products so that future research can expand the analysis on different products.